​40Ar/39Ar geochronology of terrestrial pyroxene - Ware, B.; Jourdan, Fred (Pergamon, 2018)
Geochronological techniques such as U/Pb in zircon and baddeleyite and 40Ar/39Ar on a vast range of minerals, including sanidine, plagioclase, and biotite, provide means to date an array of different geologic processes. Many of these minerals, however, are not always present in a given rock, or can be altered by secondary processes (e.g. plagioclase in mafic rocks) limiting our ability to derive an isotopic age. Pyroxene is a primary rock forming mineral for both mafic and ultramafic rocks and is resistant to alteration process but attempts to date this phase with 40Ar/39Ar has been met with little success so far.